High-temperature electrolysis of simulated flue gas in solid oxide electrolysis cells - Zheng, Yifeng (2020)
The feasibility of the solid oxide electrolysis cell (SOEC) electrolysis of flue gas based on an electrolyte-supported LSCM-GDC/SSZ/LSCF-GDC (LSCM: La0.75Sr0.25Cr0.5Mn0.5O3-δ) single cell is comprehensively evaluated. Current density-voltage curves (I-V) and electrochemical impedance spectroscopy data (EIS) are recorded to characterize the electrochemical performance of SOEC. The results confirmed that the LSCM-GDC fuel electrode is chemically stable in the flue gas atmosphere. The results also showed that simulated SO2 with concentration of 15 ppm in the flue gas has a negligible influence on the cell at an electrolysis current density of ∼0.2 A cm−2. The O2 in the flue gas increases the electrolysis activity in the fuel electrode, thereby improving the efficiency of the SOEC electrolysis of flue gas. The co-existence of SO2 and O2 in flue gas can increase the electrolysis activity of SOEC electrolysis. The total resistance of the SOEC single cell at 800 °C under OCV is 2.21 Ω cm2, indicating that the SSZ-electrolyte-supported SOEC can be practically used for the effective SOEC electrolysis of flue gas containing SO2 and O2. The cell showed a stable voltage of 1.201 V for more than 100 h for the electrolysis of flue gas with SO2 and O2 at a current density of 0.5 A cm−2 and at a temperature of 800 °C. The post-mortem analysis showed that the microstructures of all cell components are stable after the SOEC long-term durability test.